2020
DOI: 10.1002/14651858.cd006768.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for convergence insufficiency: a network meta-analysis

Abstract: Editorial group: Cochrane Eyes and Vision Group. Publication status and date: New search for studies and content updated (conclusions changed), published in Issue 12, 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 91 publications
1
28
0
Order By: Relevance
“…The overall success rate of 71% after 12 weeks was comparable to previous studies in which vergence and monocular accommodation exercises had been combined for the entire treatment period. 7 Among the participants with partial recovery and among nonresponders, the improvement of objective measures (82.4%) was better than that of subjective measures (52.9%; data not shown) suggesting that acquired oculomotor skills may have required conscious efforts with a consequent induction of fatigue. 18 , 19 This suggests that an extension of the treatment period beyond 12 weeks might have been beneficial for a minority of the children.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The overall success rate of 71% after 12 weeks was comparable to previous studies in which vergence and monocular accommodation exercises had been combined for the entire treatment period. 7 Among the participants with partial recovery and among nonresponders, the improvement of objective measures (82.4%) was better than that of subjective measures (52.9%; data not shown) suggesting that acquired oculomotor skills may have required conscious efforts with a consequent induction of fatigue. 18 , 19 This suggests that an extension of the treatment period beyond 12 weeks might have been beneficial for a minority of the children.…”
Section: Discussionmentioning
confidence: 85%
“… 4 Several studies have shown that school children diagnosed with CI have abnormal accommodation, 5 , 6 which is reflected in clinical guidelines for the treatment of CI that include exercises for both monocular accommodation and vergence, the latter including exercises for antisuppression and awareness of diplopia. 7 The effect of exercises aimed at improving vergence is assessed by measuring positive fusional vergence, vergence facility, and near point of convergence, whereas the effect on accommodation is assessed by measuring amplitude of accommodation and accommodation facility. 8 It has been shown that these measures of vergence and accommodation develop independently of each other in the age group of 7 to 15 year olds.…”
mentioning
confidence: 99%
“…The use of vectograms in vision therapy is a common procedure to improve vergence fusional ranges and step vergences [ 1 , 2 , 3 , 4 , 7 ]. In natural conditions (dual closed loop), multiple monocular and binocular cues, such as target blur, disparity, and proximity, elicit accommodative and vergence responses [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vision therapy has been employed in optometry to effectively improve binocular dysfunctions such as convergence insufficiency [ 1 , 2 , 3 , 4 ] and accommodative insufficiency [ 5 ]. Target blur, disparity, and proximity may be minutely altered through visual therapy to normalize the accommodative system, the vergence system and their interactions [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment of the convergence-insufficiency type X(T) includes RR, modified RR, slanted or nonslanted BLR (upper horn based on distance deviation angle and lower horn based on near deviation angle), slanted or non-slanted uni-/bilateral medial rectus (UMR/BMR) resection with or without an adjustable suture, and medial rectus plication [20,21,24,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. The corresponding success rates ranged from 18 to 92%, and most studies concluded that the duration of consecutive esotropia or diplopia was shorter than 4 weeks, with a tendency to exodrift with time following any of the surgical methods.…”
Section: Surgical Treatment In Convergence-insufficiency Type X(t)mentioning
confidence: 99%